O impacto do Serviço Social em uma Delegacia Especializada no Atendimento à Mulher - Filipe da Silva (2019)
A significant number of women, every day, are subjected to some form of violence. In Brazil, among the various initiatives to overcome this reality, we can mention the enactment of Law no. 11.340 / 2006 (Maria da Penha Law) and the creation of Specialized Police Offices for Women (DEAMs). The DEAM of Contagem-MG, in a pioneer and unique way in the state of Minas Gerais with regard to breaking the paradigm of “exclusive policeman” in a police station, chose to incorporate in its front line, a Social Worker (effective), responsible first assistance to the victim. Objective: To analyze the profile of domestic violence against women in Contagem-MG, comparing the cases attended by the DEAM Social Service with those recorded in the General Police Base of that municipality, from March 1, 2016 to February 29 2019. Methodology: Cross-sectional study, with a quantitative approach, using two secondary databases: 1) the Occurrence Bulletins - Record of Social Defense Events (REDS) of domestic violence against women in the municipality of Contagem / MG; 2) reception worksheet generated by the Social Service Professional from the Specialized Police Station for Women (DEAM) in the same municipality. Results: In more than half of the registered cases, in both data sources, the victims are in the age group between 20 and 39 years old, are self-declared brown and have completed high school. The perpetrators of the violence practiced are mostly people with whom the victim maintains or maintained an intimate affective relationship. Among the violence, physical and psychological violence stand out more significantly. Of every 08, of the victims who registered police reports, only 03 turned to DEAM for the first assistance. Of the victims who were first attended by the PMMG or “Common Police Station”, 74.5% worked only on REDS and did not represent criminally. The rate of disinterest in criminal representation of victims who went to DEAM is much lower (0.8%). Almost half of the cases (43%) attended by the DEAM Social Worker correspond to “extrapolic activities” or “merely social”. The rate of recidivism of victims who were treated by DEAM was lower to the detriment of those who were treated at other agencies. Conclusion: DEAM is a space permeated with demands of a social nature. This signals the importance of this equipment having a multidisciplinary team, whose purpose is not to overlap functions but to work together and in partnership between Social Workers and police. In this research it was clear that the welcoming model carried out by the Social Service provides specialized and humanized listening for the victim, providing filtering and directing cases of police and extrapolic demands, in addition to allowing investigators to dedicate themselves exclusively to the various investigative stages of the investigation police officer. Knowing the real profile of violence in the municipality will allow the search for new social strategies, allowing the improvement of the social visibility of the problem, as well as the network of coping, care and care for women in situations of violence.